The Effect of Problematic Smartphone Use on Physical Activity Level and Musculoskeletal Pain - Unver, Fatma; Buke, Meryem (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Objectives The aim of this study was to examine the effects of problematic smartphone use on physical activity level and musculoskeletal pain.Methods Two hundred eighty university students (185 female; 95 male; mean age: 20.84±2.37 years) were included in the study. The International Physical Activity Questionnaire was used to determine the level of physical activity. Problematic smartphone use was determined using the Smartphone Addiction Scale-Short Form (SAS-SF) and musculoskeletal pain using the Nordic Musculoskeletal System Questionnaire.Results When SAS-SF scores were examined, it was seen that 31.8% (89 people) of the participants had problematic smartphone use. A moderate negative correlation was found between problematic smartphone use and physical activity level (p=0.0001; r=−0.419). Neck (p=0.017) and back pain (p=0.040) severity was higher in people with problematic smartphone use.Conclusions The findings show that problematic smartphone use has negative effects on both physical activity level and pain severity. For this reason, problematic smartphone use should be questioned in university students with neck and back pain.
Keywords: addiction; pain; physical activity; smartphone